Development and Psychometric Evaluation of the Cardiac Rehabilitation Adherence Tool (CRAT) - Mojtaba Vaismoradi (Journal of Cardiovascular Development and Disease, 2019)
Patients with cardiac diseases can achieve the greatest benefit from cardiac rehabilitation through modification of their unhealthy behaviors. This study aimed to develop and examine the psychometric properties of the Cardiac Rehabilitation Adherence Tool (CRAT), which was designed to assess patients’ adherence to cardiac rehabilitation. In this instrument development study, the items of the CRAT were extracted through a comprehensive literature review. The CRAT was assessed in terms of validity and reliability. Exploratory factor analysis was conducted to assess its construct validity, which led to the development of a tool containing 57 items and five dimensions including “acceptance of the rehabilitation center,” “being interested in health,” “feeling a need,” “personal control over the situation,” and “encouragement and advice.” These five factors accounted for 45.23% of the observed variance. The Cronbach’s alpha was 0.935. The test-retest method supported the stability of the instrument (r = 0.95). Health care professionals can use the CRAT to examine factors influencing the patient’s decision to leave cardiac rehabilitation and design strategies for improving their adherence to the rehabilitation program.